2010
DOI: 10.1164/rccm.200905-0659oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lung Apolipoprotein A-I in Idiopathic Pulmonary Fibrosis

Abstract: Alterations of several inflammatory and antiinflammatory proteins in the lungs may be related to the pathogenesis of IPF, and local treatment with Apo A-I is very effective against the development of experimental lung injury and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…The functional role of APOA2, the most downregulated differentially expressed proteins identified in the present study, has not been reported in IPF in the past. However, low concentrations APOA1 were found in bronchoalveolar lavage fluids from subjects with IPF [48]. This suggested the involvement of APOA2 in the pathophysiology of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of APOA2, the most downregulated differentially expressed proteins identified in the present study, has not been reported in IPF in the past. However, low concentrations APOA1 were found in bronchoalveolar lavage fluids from subjects with IPF [48]. This suggested the involvement of APOA2 in the pathophysiology of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…BAL had been performed in the most affected lobe by computed tomography in the 24 subjects without any immunosuppressive therapy and in the right middle lobe of 14 normal controls, as described previously[17]. The supernatant was separated from cell pellets by centrifugation at 500 × g for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…There is emerging evidence that Apo A-I has a critical role in protecting pulmonary artery and airway function as well as preventing inflammation and collagen deposition in the lung (33). Local treatment with Apo A-I is very effective against the development of experimental lung injury and fibrosis (34). Intermittent hypoxic exercise has been shown to stimulate the levels of Apo A-I and strengthen the metabolism of lipids, and may have certain functions in cardiovascular disease treatment (35).…”
Section: Discussionmentioning
confidence: 99%